Does Acute Appendicitis in Pregnancy a Clinical Challenge in Surgery Practice? Our Experience - Bolukbasi, Hakan; Yilmaz, Serhan; Yildirim, Engin Okan; Ocakoğlu, Aziz (Lietuvos chirurgija, 2022)
Objective. This study was designed to compare the diagnosis, treatment, and results of acute appendicitis in pregnant and non-pregnant women. Material and Methods. Women between the ages of 18 and 40 who were operated for acute appendicitis between 2015 and 2020 were included in the study. Results. There were 27 (3.8%) patients in Group Pregnant, and 679 (96.2%) patients in Group non-Pregnant. The mean WBC values in Group P and Group non-P was 16.53±2.91 and 13.99±4.31 (x103), and there was a significant difference between the groups.Mean pain symptom duration time was 3.40±1.90 in Group P and 1.91±1.34 day in Group non-P, while it was significantly longer in Group P . When the preoperative USG reports were evaluated, no significant difference was found between the groups.The diagnosis was made by MRI in 2 (7.4%) pregnant patients who non-visualized according to the USG report. In Group P, 10 patients were laparoscopic, 17 patients open; In group non-P, 153 patients laparoscopic and 526 patients were operated using open surgery technique. While the mean operation time did not differ significantly between the groups. Length of hospital stay was significantly higher in Group P with 3.48±4.26 days to 1.95±1.45 days. Conclusion. Diagnosis and treatment of acute appendicitis during pregnancy may be difficult, but with advanced radiological examinations and experienced surgeons, these difficulties can be easily overcome.